Catholic Education Foundation: Prophecy, project and transformation. Reaffirm commitment and update mission (Journal of Parents and Teachers, 2017)
25 years ago appeared in Spain a phenomenon which was unknown. The religious institutions, owners of hundreds of schools throughout our geography, began to glimpse the situation we are in now: few vocations, the desire to continue with the educational works and the responsibility to assume truly the shared mission together with the laity. The Catholic Education Foundation was born, a prophecy that over the years has been consolidated in a transformative and avant-garde educational project
Keywords: Catholic Foundation; educational project; innovation; educational improvement.